Implikasi Pedagogi Paulo Freire dan Antonia Harder Terhadap Tindak Pidana Perdagangan Manusia di Nusa Tenggara Timur - Jear Nenohai (Institut Agama Kristen Negeri Toraja, 2021)
Current research on human trafficking in the Christian Evangelical Church in Timor (GMIT) does not currently involve an educational approach to analyze the problem. So, the aim of this article is to contribute ideas about the pattern of contextual education for GMIT in countering human trafficking cases in East Nusa Tenggara. This study is based on a literature study comparing the critical pedagogy of Paulo Freire and Antonia Harder. After that, the authors uses this pedagogy to analyze the praxis of the mission of the Christian Evangelical Church in Timor and the contextual education practices of an alternative school named Lakoat.Kujawas. Through the mission and education dialogue, the authors see that the resistance base of GMIT has not involved culture and nature as a basis for resistance. Through the critical pedagogical analysis of Freire and Antonia Harder, the author shows the relevance of Lakoat.Kujawas’s liberation pedagogy and contextual education model for the resistance process undertaken by GMIT. Finally, this research is limited to the exploration of critical pedagogy for cases of human trafficking and not involve further politic of education, intercultural theological and practical studies on the pedagogy of liberation. AbstrakPenelitian tindak pidana perdagangan orang oleh Gereja Masehi Injili di Timor sejauh ini belum melibatkan pendekatan pendidikan di dalamnya. Oleh karena itu, tujuan artikel ini ialah membedah perdagangan orang dari sudut pandang pendidikan dan memberikan kontribusi pendekatan pendidikan terhadap pengembangan perlawanan Gereja Masehi Injili di Timor kasus perdagangan orang di Nusa Tenggara Timur. Penelitian ini didasarkan pada studi pustaka dengan mengandalkan pendekatan pedagogi pembebasan Paulo Freire dan Antonia Harder. Ide kedua tokoh tadi penulis pakai untuk menganalisa praksis misi perlawanan yang dikerjakan oleh Gereja Masehi Injili di Timor. Melalui tulisan ini, penulis menunjukan bahwa dengan mengembangkan praktik pendidikan, Gereja Masehi Injili di Timor mampu mengembangkan perlawanan yang berciri membebaskan, dan berdimensi multi keilmuan dengan mengandalkan konteks warga Gereja agar Gereja Masehi Injili di Timur mampu mendidik warga Gereja agar tidak lagi menjadi pelaku perdagangan orang.